Using physical contact heterogeneity and frequency to characterize dynamics of human exposure to nonhuman primate bodily fluids in central Africa. - Victor Narat; Mamadou Kampo; Thibaut Heyer; Stephanie Rupp; Philippe Ambata; Richard Njouom; Tamara Giles-Vernick (Public Library of Science (PLoS), 2018)
Emerging infectious diseases of zoonotic origin constitute a recurrent threat to global health. Nonhuman primates (NHPs) occupy an important place in zoonotic spillovers (pathogenic transmissions from animals to humans), serving as reservoirs or amplifiers of multiple neglected tropical diseases, including viral hemorrhagic fevers and arboviruses, parasites and bacteria, as well as retroviruses (simian foamy virus, PTLV) that are pathogenic in human beings. Hunting and butchering studies in Africa characterize at-risk human social groups, but overlook critical factors of contact heterogeneity and frequency, NHP species differences, and meat processing practices. In southeastern Cameroon, a region with a history of zoonotic emergence and high risk of future spillovers, we conducted a novel mixed-method field study of human physical exposure to multiple NHP species, incorporating participant-based and ecological methodologies, and qualitative interviews (n = 25). We find frequent physical contact across adult human populations, greater physical contact with monkeys than apes, especially for meat handling practices, and positive correlation of human exposure with NHP species abundance and proximity to human settlement. These fine-grained results encourage reconsideration of the likely dynamics of human-NHP contact in past and future NTD emergence events. Multidisciplinary social science and ecological approaches should be mobilized to generate more effective human and animal surveillance and risk communications around neglected tropical diseases. At a moment when the WHO has included "Disease X", a presumably zoonotic pathogen with pandemic potential, on its list of blueprint priority diseases as, new field-based tools for investigating zoonotic disease emergence, both known and unknown, are of critical importance.